Analysis of Working Time Measurement and Incentives Work to Increase Shoe Upper Production at CV. Esa Kalen Jaya - Agustin, Putri Olivia; Rusindiyanto, Rusindiyanto (Journal La Multiapp, 2024)
As time goes by, competition in the industrial world is increasing, every company is required to be able to compete with other companies. CV.Esa Kalen Jaya is a company that produces semi-finished goods, namely shoe uppers. Where there are obstacles in the form of not being able to fulfill the production targets that have been determined by the company which results in the company's productivity not being optimal. This research was conducted to calculate standard production time through direct observation using a stopwatch time study as well as improving the regulation of the number of working hours and providing work incentives using the piecework plan method. as an effort to increase company productivity.. Results obtained. The standard output obtained is 4588.48 units/month. And after increasing the number of production working hours to 8 working hours, the results were 5,234 units/month, which means the production target has been achieved. And based on the calculation of incentives that the company will provide in standard hourly wages, namely IDR 7,051.41/hour. It can be concluded that by determining the standard production time and determining the number of working hours, the production results have achieved the set production targets.